THE INTEGRATION OF RELIGIOUS MODERATION VALUES IN ISLAMIC EDUCATION MANAGEMENT - Asfiyah, Wardatul; Anggraeni, Aprilia Fentika Dewi Gita (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
Religious moderation has become a key strategy in responding to the growing challenges of intolerance and radicalism, particularly within Islamic educational settings. This article aims to analyze how the values of religious moderation are integrated into Islamic education management through the framework of public policy. The study employs a library research method with content analysis of key documents such as Presidential Regulation No. 58 of 2020 on the Strengthening of Religious Moderation and the National Action Plan for the Prevention of Extremism (RAN PE) 2020–2024. The findings indicate that these policies promote the development of an inclusive institutional vision, the reinforcement of a moderate curriculum, and an evaluation system that instills the values of tolerance. However, policy implementation in the field still faces challenges such as limited human resources and suboptimal institutional synergy. This study emphasizes the importance of consistent regulatory support, continuous training, and collaboration among the government, educational institutions, and society to ensure that religious moderation is effectively implemented in the governance of Islamic education. Thus, religious moderation becomes not only a part of policy discourse but also an ethical foundation for the development of peaceful, inclusive, and sustainable Islamic education.